Altered expression and potential role of N6-methyladenosine mRNA methylation in abdominal aortic aneurysm mouse model - Julin Wang; Tianyu Miao; Yanyun Wang; Tiehao Wang; Zhangyu He; Fei Xiong; Ding Yuan; Qiang Guo; Yi Yang; Zhichen Tang; Bin Huang; Jichun Zhao (Scientific Reports)
Abstract It is an important cause of death in old age to rupture an abdominal aortic aneurysm. The pathogenesis of AAA has not been fully elucidated, and m6A RNA methylation regulators have never been implicated in AAA development. This study aimed to explore the expression profile, potential functions and regulated mechanism of m6A RNA methylation in the abdominal aortic aneurysm mice model. A successful AAA mouse model was established using Ang II. M6A- methylated RNA Immunoprecipitation (MeRIP) sequencing and RNA sequencing were performed to identify the m6A sites in the abdominal aorta walls samples. The expression of m6A methylation regulators was analyzed in the datasets and MeRIP-qPCR was performed to verify the results of MeRIP-sequencing. Bioinformatics analysis was used to evaluate the m6A patterns and indicate the potential signaling pathway. There were 2039 differentially methylated m6A peaks involving 1865 mRNAs in the AAA group relative to the control, of which 1610 peaks in 1466 mRNAs were hypermethylated, and 429 peaks in 410 mRNAs were hypomethylated. The hypermethylated mRNAs in AAA group were primarily enriched in transcription regulation and intercellular signaling, especially the Wnt signaling-associated processes. Hypomethylated m6A sites were mainly enriched in G protein-coupled receptor activity and ion channel activity. MeRIP-qPCR suggested that the sequencing data were reliable and accurate. The mRNA expression of 24 m6A regulators showed no obvious difference between AAA and the control group, but the m6A methylation levels of three components of methyltransferases complex and one ‘readers’ were significantly increased. Our study suggested an original viewpoint that the m6A modification might be regulated by several unidentified regulation modes or genes in the Ang II-induced AAA mice model, and be closely relevant to the combined effect of m6A methylation modification in the Wnt pathway, G protein-coupled receptor, and ion channel-associated genes, which were worthy of further investigation.